(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article provides information about the winter wheat varieties found in the Bukhara region. Winter wheat is a grain crop resistant to cold and characterized by high productivity. It is typically sown in the autumn and harvested in the summer of the following year. It has a longer growing season compared to spring wheat, producing a more abundant harvest and higher grain quality.